QSO obscuration at high redshift (z ≳ 7): predictions from the bluetides simulation. Issue 2 (11th May 2020) - Ni, Yueying; Di Matteo, Tiziana; Gilli, Roberto; Croft, Rupert A C; Feng, Yu; Norman, Colin
ABSTRACT: High-z AGNs hosted in gas-rich galaxies are expected to grow through significantly obscured accretion phases. This may limit or bias their observability. In this work, we use bluetides, a large volume cosmological simulation of galaxy formation to examine quasar obscuration for the highest redshift (z ≥ 7) supermassive black holes residing in the centre of galaxies. We find that for the bright quasars, most of the high-column density gas ( 90 per cent ) resides in the innermost regions of the host galaxy (typically within <10 ckpc), while the gas in the outskirts is a minor contributor to the N H . The brightest quasars can have large angular variations in galactic obscuration, over 2 orders of magnitude (ranging from column density N_H 10^21.5 \!-\! 24 cm^-2 ), where the lines of sight with the lowest obscuration are those formed via strong gas outflows driven by AGN feedback. The obscured fraction P ( N H > 10 23 cm −2 ) typically ranges from 0.6 to 1.0 for increasing L X (with L_ X 10^43 erg s^-1 ), with no clear trend of redshift evolution. Due to the angular variation in N H, all relations between N H and L X, M BH, and galaxy host properties (global M *, M_H_2, and star formation rate) show appreciable scatter. The dust optical depth in the UV band τUV has tight positive correlation with N H . Our dust-extincted UV luminosity function (UVLF) is about 1.5 dex lower than the intrinsic UVLF, implying that more than 99 per cent of the z ∼ 7 AGNs are heavily dust extincted and therefore would be missed by the UV-band observation.